SISTEM DATA MINING UNTUK MENGETAHUI TINGKAT KECENDERUNGAN MEMILIH MENU MAKANAN DENGAN METODE ASSOCIATION RULE MINING (STUDI KASUS : KEDAI KEMANGI) - Raymond Octhario; Sri Karnila (Jurnal Informatika, 2013)
Data mining is a term that used to discover hidden knowledge in the database. Data mining is a semi-automatic process that uses statistical techniques, mathematics, artificial intelligence, and machine learning to extract and identify potential useful information and knowledge that stored in large databases. One of methods in data mining is association rule method where this method will looking for a set of items that frequently occur together. This method is often analogous as shopping cart which can be known, what items are frequently purchased together and which items are not. The advantage of this method can be utilized to determine amount of inventory that must be provided in a business. In this paper will be made of a mining system that will show the trend of buyers in a restaurant so that decision-makers will be able to determine amount of groceries accordance with the business need to minimize losses. Keywords : Data Mining, association rule